Divorce factors during the Covid-19 pandemic at Pangkalan Bun religous court class 1B - Putri Ayi Winarsasi; Adelia Astiani (Trigin Publisher, 2023)
The definition of marriage in the provisions of Article 1 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and happy family or household. eternal life based on God Almighty. Marriage is expected to last forever and be done once in a lifetime without any divorce. However, in reality, divorce is inevitable. Divorce that occurs can be caused by many factors. The research method used by the author in this study is empirical legal research. This study aims to find out what factors can lead to divorce during the Covid-19 pandemic, which occurred at the Pangkalan Bun Religious Court Class IB. According to the study's findings, the factors that affect divorce include economic issues by 45.5%, adultery by 28.5%, marital dispensation by 18.5%, parents are excessively intrusive by 5%, and another factor of 2.5%, such as one partner having an aberration in his sexual orientation.